Cytokine response signatures in disease progression and development of severe clinical outcomes for leptospirosis. - Eliana A G Reis; José E Hagan; Guilherme S Ribeiro; Andrea Teixeira-Carvalho; Olindo A Martins-Filho; Ruth R Montgomery; Albert C Shaw; Albert I Ko; Mitermayer G Reis (Public Library of Science (PLoS), 2013)
Background The role of the immune response in influencing leptospirosis clinical outcomes is not yet well understood. We hypothesized that acute-phase serum cytokine responses may play a role in disease progression, risk for death, and severe pulmonary hemorrhage syndrome (SPHS). Methodology/principal findings We performed a case-control study design to compare cytokine profiles in patients with mild and severe forms of leptospirosis. Among patients hospitalized with severe disease, we compared those with fatal and nonfatal outcomes. During active outpatient and hospital-based surveillance we prospectively enrolled 172 patients, 23 with mild disease (outpatient) and 149 with severe leptospirosis (hospitalized). Circulating concentrations of pro- and anti-inflammatory cytokines at the time of patient presentation were measured using a multiplex bead array assay. Concentrations of IL-1β, IL-2, IL-4, IL-6, IL-8, IL-10, IL-17A, and TNF-α were significantly higher (P<0.05) in severe disease compared to mild disease. Among severe patients, levels of IL-6 (P<0.001), IL-8 (P = 0.0049) and IL-10 (P<0.001), were higher in fatal compared to non-fatal cases. High levels of IL-6 and IL-10 were independently associated (P<0.05) with case fatality after adjustment for age and days of symptoms. IL-6 levels were higher (P = 0.0519) among fatal cases who developed SPHS than among who did not. Conclusion/significance This study shows that severe cases of leptospirosis are differentiated from mild disease by a "cytokine storm" process, and that IL-6 and IL-10 may play an immunopathogenic role in the development of life-threatening outcomes in human leptospirosis.